Static strength of collar plate reinforced tubular T/Y-joints under brace compressive loading. (March 2016) - Nassiraei, Hossein; Lotfollahi-Yaghin, Mohammad Ali; Ahmadi, Hamid
Abstract: In the present paper, the static strength of steel collar plate reinforced tubular T/Y-joints is numerically investigated. A finite element (FE) model was developed and the results were verified against the experimental data. Afterwards, a set of 168 FE models of collar plate reinforced T/Y-joints was generated and analyzed under axially compressive loads. The effect of plate size and joint geometry on the ultimate strength and failure mechanism of the joints were investigated through a parametric study. Results showed that the ultimate strength of a collar plate reinforced T/Y-joint can be up to 270% of the strength of the corresponding unreinforced joint. Despite this significant difference between the static strength of unreinforced and collar plate reinforced T/Y-joints, studies on this type of reinforced joints have been limited to very few T-joint tests. Also, no design equation is available to determine the ultimate strength of T/Y-joints reinforced with collar plates. Hence, after the parametric study, a new equation is proposed, through nonlinear regression analysis, for determining the ultimate strength of collar plate reinforced T/Y-joints under axially compressive loads. Highlights: The ultimate strength and failure modes of collar plate reinforced tubular T/Y-joints under axial load were studied. 168 FE models were developed for the parametric study of geometrical effects on the ultimate strength. Geometrical effects on the failure modes under axially compressive loads were studied. Significant difference exists between the static strength of unreinforced and collar plate reinforced joints. A parametric equation was proposed for the calculation of the strength ratio in reinforced T/Y-joints.